Complete greenhouse dynamic simulation tool to assess the crop thermal well-being and energy needs. (October 2020) - Baglivo, Cristina; Mazzeo, Domenico; Panico, Simone; Bonuso, Sara; Matera, Nicoletta; Congedo, Paolo Maria; Oliveti, Giuseppe
Highlights: TRNSYS software is expanded for the standard and detailed greenhouse thermodynamic simulation. Thermal predictions are in excellent agreement with those of another recognized software. Greenhouse free-cooling control and air flows strongly depend on the volume discretization. The standard model is only accurate in the free-floating regime for the crop well-being evaluation. The most detailed tool accurately assesses the greenhouse cooling and heating energy needs. Abstract: Greenhouse technology is an important energy consumer sector representing an indispensable solution for modern methods of crop production. In the greenhouse envelope and system design phase, thermodynamic performance simulation tools are required. The greenhouse simulation is still a very complex task despite many building tools are available in the literature. This work aims to overcome this gap by proposing a reference methodology to accommodate the building TRNSYS software for a greenhouse able to consider simultaneously different thermal phenomena with detailed modelling of: dense volume discretization, 3D shortwave and longwave radiative exchange, air flow exchanges, presence of lamps with their exact 3D position, ground and plant evapotranspiration, and convective heat transfer coefficients. A standard hourly simulation of the one-zone greenhouse was validated with another recognized tool, showing excellent agreement throughout the year. The main parameters affecting the greenhouse thermal balance were investigated in both a free-floating and continuous regime. The investigation has shown that a standard simulation is accurate to only reproduce the thermal response in a free-floating regime; instead, the detailed simulation has led to overall cooling and heating energy needs in the continuous regime, respectively, of 51.4 kWh/m 3 and 49.1 kWh/m 3, avoiding to obtain very high errors.